2017
DOI: 10.1128/aac.00086-17
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Resistance Selection in Shigella flexneri by Azithromycin, Ceftriaxone, Ciprofloxacin, Levofloxacin, and Moxifloxacin

Abstract: Shigella flexneri continues to be a major cause of diarrhea-associated illness, and increasing resistance to first-line antimicrobials complicates the treatment of infections caused by this pathogen. We investigated the pharmacodynamics of current antimicrobial treatments for shigellosis to determine the likelihood of resistance promotion with continued global antimicrobial use. The mutant prevention concentration (MPC) and mutant selection window (MSW) were determined for azithromycin, ceftriaxone, ciprofloxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
5
3
0
Order By: Relevance
“…These data pairs include the MIC and the corresponding MPC, of various antimicrobial agents with different classes against representative pathogenic bacteria, and shown in Table S5. After this, using another forty-six data pairs (MIC, MPC) (Table S6) reported from other papers [38][39][40][41][42], this correlation was further verified by comparison the calculated MPC with the tested one.…”
Section: Correlation Between the Mpc And The Mic Of An Antimicrobial ...supporting
confidence: 59%
See 1 more Smart Citation
“…These data pairs include the MIC and the corresponding MPC, of various antimicrobial agents with different classes against representative pathogenic bacteria, and shown in Table S5. After this, using another forty-six data pairs (MIC, MPC) (Table S6) reported from other papers [38][39][40][41][42], this correlation was further verified by comparison the calculated MPC with the tested one.…”
Section: Correlation Between the Mpc And The Mic Of An Antimicrobial ...supporting
confidence: 59%
“…Thereby, we can simultaneously use equations ( 7) and ( 8), or other equations established like similar method, to quickly and complementarily predict the rough MPCs from the MIC as references when need. This was further verified by another forty-six data pairs (MIC, MPC) (Table S6) from another five papers [38][39][40][41][42], with an acceptable probability of 91.3%. Conversely, the larger prediction accuracy further confirmed that the MPC of an antimicrobial agent can be roughly calculated from its corresponding MIC.…”
Section: Correlation Between the Mpc And The Mic Of An Antimicrobial ...supporting
confidence: 55%
“…Thereby, we can simultaneously use equations ( 7) and (8), or other equations established like similar method, to quickly and complementarily predict the rough MPCs from the MIC as references when need. This was further verified by another forty-six data pairs (MIC, MPC) (Table S7) from another five papers [42][43][44][45][46], with an acceptable probability of 91.3%. Conversely, the larger prediction accuracy further confirmed that the MPC of an antimicrobial agent can be roughly calculated from its corresponding MIC.…”
Section: Correlation Between the Mpc And The Mic Of An Antimicrobial ...supporting
confidence: 55%
“…It has been recommended by the American Academy of Pediatrics for treatment of shigellosis in children and by the World Health Organization as a second-line treatment in adults. However, recent reports have suggested that there are Shigella isolates that are not susceptible to azithromycin (4,9,10).…”
mentioning
confidence: 99%